Pelatihan Gejog Lesung pada Pemuda Dusun Gunturan, Triharjo, Pandak, Bantul Sebagai Upaya Pelestarian Budaya Bangsa - Suprapto, Wasis; Kariadi, Dodik (Universitas Nusantara PGRI Kediri, 2018)
Bantul is one of the areas in the special region of Yogyakarta which is rich with traditional art one of them is art gejoglesung. This folk art comes from the sound of pounded alupukulkan regularly on large woods made like a boat called mortar. In general, dimples made of jackfruit wood or munggur. Nowadays gejoglesung art began to be abandoned by its lover because it is unable to compete with modern art. Therefore, we are moved to preserve the art of gejog mortar in order not to become extinct. One way is to hold gejog lesung training on youth youthgunturan, triharjo, pandak, bantul. The method of implementing the training is done through three stages of preparation, implementation, and follow-up. The preparation stage includes socialization, participant data collection, and training design. Implementation phase includes acceptance of participants, practice training, gejog art performances mortar. Theresults ofthis trainingwas able to foster back the sense of brotherhood, togetherness, cooperation, responsibility, nationalism among gejoglesung players themselves. This training was followed not only young men but also children, even parents participate and enliven the arts of the people. Gejoglesung training is a medium to re-preserve Bantul art that is almost extinct eroded by the times.